The unsteady flow features behind a heliostat in a narrow channel at a high Reynolds number: Experiment and Large Eddy Simulation. (February 2018) - Boddupalli, Nibodh; Yadav, Navneet Kumar; Chandra, Laltu
Highlights: Flow induced- dust deposition on heliostat, erosion of mirror coating will lead to the failure of a concentrated solar thermal system; Wake behind a heliostat is investigated using large eddy simulation and Laser Doppler Velocimetry at a high Reynolds number of ca. 60, 000; Unsteady flow features including flow development, coherent structures and the associated physics are discussed; Energy re-distribution in the large-scale (low-frequency) motions are observed using fourier analysis; Organization of span-wise vorticity in the wake along with the streamlines is presented, which are likely to promote local deposition as observed in a reported experiment. Abstract: Several heliostats are arranged on the field for concentrating beam solar radiation onto a receiver. The flow-induced dust deposition and vibration of heliostats will lead to failure of the receiver and the entire system in eventuality. Therefore, fluid flow analysis behind a heliostat model in a narrow channel of limited length is presented depicting a field-type condition. In this paper, experiment and Large Eddy Simulation (LES) are performed. Laser Doppler Velocimetry (LDV) technique is used for horizontal velocity measurement around a heliostat with 25° angle of inclination at a Reynolds number of 60, 000 basing on the length of an inclined plate. The wall-resolved coarse, intermediate and fine grids are utilized for LES with dynamic- Smagorinsky–Lilly and subgrid-scale kinetic energy transport equation based models. Comparison between local instantaneous and statistical quantities, like horizontal velocity and its root-mean-square values are presented. The flow development in the wake region of heliostat model is described using the time-dependent and the statistical horizontal velocity. Based on the adopted LES approach the coherent structures are identified with the λci -criterion. The analysis of power spectral density and swirling strength isosurface reveal the responsible coherent structures in the inertial subrange for transport of energy to smaller structures. Interestingly, the presence of hairpin-type vortices is observed extending from the two sides of model heliostat using the λci -criterion. Further, instantaneous span-wise vorticity contour reveals their alignment with flow represented by streamlines. The provided insight to these flow features and their organization is expected to frame strategies for mitigating the unsteady flow-induced vibrations and dust depositions on heliostats. Graphical abstract: Figure: (a) Experiment and computation setup (b) Swirling strength isosurface (λci -criterion) (c) hairpin-type structures (d)Instantaneous spanwise-vorticity contour with streamlines.